Chapter 5 Long-Range Regulation of α-Globin Gene Expression - Higgs, D; Vernimmen, D; Wood, B (2008)
Over the past 20 years, there has been an increasing awareness that gene expression can be regulated by multiple cis-acting sequences located at considerable distances (10-1000 kb) from the genes they control. Detailed investigation of a few specialized mammalian genes, including the genes controlling the synthesis of hemoglobin, provide important models to understand how such long-range regulatory elements act. In general, these elements contain a high density of evolutionarily conserved, transcription factor-binding sites and in many ways resemble the upstream regulatory elements found adjacent to the promoters of genes in simpler organisms, differing only in the distance over which they act. We have investigated in detail how the remote regulatory elements of the α-globin cluster become activated as hematopoietic stem cells (HSCs) undergo commitment, lineage specification, and differentiation to form red blood cells. In turn, we have addressed how, during this process, the upstream elements control the correct spatial and temporal expression from the α-gene promoter which lies ∼60 kb downstream of these elements. At present too few loci have been studied to determine whether there are general principles underlying long-range regulation but some common themes are emerging. © 2008 Elsevier Inc. All rights reserved.